Contemporary issues in behavioral finance - Grima, Simon; Özen, Ercan; Boz, Hakan; Spiteri, Jonathan; Thalassinos, Eleftherios (Contemporary studies in economic and financial analysis ;, 2019)
This special edition of Contemporary Studies in Economic and Financial Analysis offers seventeen chapters from invited participants in the International Applied Social Science Congress, held in Turkey between the 19th and 21st April 2018. The chapters included tackle a range of issues, including risk and control in consumer behavior; augmented reality applications in brand trust; foreign exchange rates; and brand reputation influence, among many more. Covering concepts such as retirement planning, the stock market, and herd behavior, Contemporary Issues in Behavioral Finance is a fundamental text for any researcher or student of behavioral finance, with a cast of expert contributors and editors.